Cases report of unicentric Castleman's disease: revisit of radiotherapy role - Noh, O Kyu (The Korean Society for Radiation Oncology, 2013)
Castleman's disease or angiofollicular lymph node hyperplasia is a rare lymphoproliferative disorder. Complete surgical resection was recommended in unicentric Castleman's disease. Radiotherapy was considered alternative therapeutic option. However, there have been consistent favorable responses to radiotherapy. We also experienced two cases of uncentric Castleman's disease salvaged successfully with radiotherapy. This paper described these cases and reviewed the literature about Castleman's disease treated with radiotherapy. Reviewed cases showed that radiotherapy is a successful treatment option in unicentric Castleman's disease. Furthermore, our report confirms the radiotherapy role in uncentric Castleman's disease.